2023
DOI: 10.29333/iji.2023.16231a
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of RBL-STEM Learning Materials to Improve Students Historical Literacy in Designing the Indonesian Batik Motifs

Abstract: The implementation of RBL-STEM learning materials to improve students historical literacy in designing the Indonesian batik motifs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…The results show that there is a significant difference between the pre-test and post-test results, especially in the experimental class. The result is in line with the research that has been done by Hidayatul who focus in research implementation of research-based learning and the effect to the students' metacognition thinking skills in solving h-irregularity problem [ 19 ], and The implementation of RBL-STEM Learning Materials to Improve Students Historical Literacy [ 25 ]. The results showed that the descriptive data on student meta-literacy ability in the experimental class shows 10% of students have the poor meta-literacy ability, 17% of students have the fair meta-literacy ability, 26% of students have the good meta-literacy ability, 32% of students have the very good meta-literacy ability and 15% of students have the excellent meta-literacy ability.…”
Section: Discussionsupporting
confidence: 82%
“…The results show that there is a significant difference between the pre-test and post-test results, especially in the experimental class. The result is in line with the research that has been done by Hidayatul who focus in research implementation of research-based learning and the effect to the students' metacognition thinking skills in solving h-irregularity problem [ 19 ], and The implementation of RBL-STEM Learning Materials to Improve Students Historical Literacy [ 25 ]. The results showed that the descriptive data on student meta-literacy ability in the experimental class shows 10% of students have the poor meta-literacy ability, 17% of students have the fair meta-literacy ability, 26% of students have the good meta-literacy ability, 32% of students have the very good meta-literacy ability and 15% of students have the excellent meta-literacy ability.…”
Section: Discussionsupporting
confidence: 82%
“…This study uses design a Pre-test -Post-test Non-equivalent group design by using two groups/classes that are given different treatments. The design of pre-testpost-test Non-equivalent group design consist of two groups which were the experimental group and control group with different treatment (Sumardi et al, 2022). The experimental class is a class that is given treatment, i.e the implementation of PBL-STEAM equipped with Jbatik software (Yuliani, 2018).…”
Section: The Type Of Research Approach and Brief Research Proceduresmentioning
confidence: 99%
“…Research-based learning integrates theoretical knowledge with suitability in data collection and analysis procedures to examine, verify/study the phenomenon. RBL is supposed to help teachers and students be more interested in practicing and following the given subjects and be more beneficial for the study program [ 22 , 23 ]. In this study we applied the RBL syntax in Economy class.…”
Section: Introductionmentioning
confidence: 99%